RICE PADDIES ON THE WHITE HOUSE LAWN - Tricia Reville (Columbia Journal of Race and Law, 2020)
Our peaceful trading partners are not our enemies; they are our allies.  We should beware of the demagogs who are ready to declare a trade war against our friends—weakening our economy, our national security, and the entire free world—all while cynically waving the American flag.  The expansion of the international economy is not a foreign invasion; it is an American triumph, one we worked hard to achieve, and something central to our vision of a peaceful and prosperous world of freedom.[1] – President Ronald Reagan